PENGARUH SISTEM PENGENDALIAN INTERN, ASIMETRI INFORMASI, KESESUAIAN KOMPENSASI DAN IMPLEMENTASI GOOD CORPORATE GOVERNANCE TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Empiris pada Rumah Sakit Swasta yang ada di Pekanbaru) - Indra Ramadhany; Novita Indrawati; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to obtain empirical evidence about the influence of internal control system, information asymetry, suitability compensation and good corporate governance implementation to the tendency of accounting fraud. This study used primer data with quitonaiers. The population of this study was obtained from a sample of all hospital in Pekanbaru. The sample was determined using the saturated samples with unit of analysis of this study is a division of financial and procuremen, and respondent as many as 80, so the questionnaire is returned as many 52 pieces. The analysis technique used multiple linear regression analysis using SPSS ver. 17 computer program. The result of the study showed that (1) partially the internal control affected the accounting fraud, (2) partially the informational asymmetrical affected the accounting fraud, (3) partially the compliance compensation affected to the accounting fraud, (4) partially the good corporate governance implementation contributed the accounting fraud and (5) simultaneously the internal control system, the informational asymmetry, compliance compensation, and the implementation good governance significantly affected the tendency of the accounting fraud.Keyword : fraud, internal, asymetry, compensation and corporate